"Four Strategic Approaches": From a Dilemma to a Strategy for Improving the Quality of Public Education Services - HB, Amran; Kurniadi, Kurniadi (Journal La Sociale, 2023)
The implementation of policy measures aimed at granting educational autonomy to schools, so granting them substantial managerial authority, has not effectively resolved the issue at hand. School-based administration only focuses on substantive education service matters, whereas the Ministry of Education and Culture oversees public schools and the Ministry of Religion oversees religious schools. This study employs a strategic management methodology to reveal diverse perspectives on these matters inside the organization's strategic operations. Interviews conducted with 30 high-ranking officials from the two technical organizations responsible for overseeing regional education services in the province indicated that there was still a significant disparity of around 50% between the desired number of teachers in the regions and the actual number of teachers already employed. Interviews conducted with 60 school principals in various regions have revealed a significant scarcity of teachers and a prevalence of instructors with subpar qualifications. Observations and document analysis confirm the existence of objective reality, identify obstacles, and offer data for developing initiatives to enhance service quality. This study presents a problem-solving framework known as the "Four strategic approaches" to enhance the quality of educational public services. This strategy model focuses on two service components that provide challenges: (1) the provision of comprehensive educational services by school institutions, and (2) the administration of education services by the regional Ministry of Education and Culture and Ministry of Religion. The text examines the primary stakeholders in secondary education services and presents four strategies to mitigate both direct and indirect risks and provide solutions.